Telemedicine Diffusion in a Developing Country: A case of Uganda - Femi Ekanoye; Temitope Olokunde; Foluso Emmanuel Ayeni; Vekima Nina; Carole Donalds; Victor Mbarika (International Journal of Computing and Informatics (IJCANDI), 2017)
Telemedicine is the diagnosis and treatment of patients by the use of telecommunications technology. Telemedicine has become a popular technological development for long-distance health care and continuing education.Telemedicine is used to assist with giving aid in rural and remote areas that can’t afford real medical help.  In a country like Uganda that has a population of roughly 33 million people and a little over 130 districts, the rate of HIV/AIDS are rising and leaving the life expectancy to about 53 years old. Similar to countries in Africa, Uganda has a very poor healthcare. Most residents of Uganda do not live near healthcare facilities and those who do live nearby may find healthcare unaffordable.This paper captures the different case studies that have benefited Uganda, the current status of telemedicine in Uganda, and what can possibly happen in the nearest future with the rise in the use of technology in telemedicine as well as the infrastructure and need for telemedicine.